Strategi Guru TK Dalam Menjaga Perkembangan Psikologi Anak Usia Dini Di RA Al-Muhklisin Waru Timur - Faridatus Supatmi, Any; Jannah, S. Fathiyatul (Al Irsyad: Jurnal Studi Islam, 2022)
The researcher aims to find out (1) how kindergarten teacher Guidance Strategies in maintaining Early Childhood Development, (2) teacher constraints in maintaining early childhood development, and (3) supporting factors for early childhood psychological development. This study uses a qualitative research method with a case study research design. The data collection techniques in this study included interviews, observation, and documentation. The data analysis techniques in this study were data reduction and data presentation drawing. The results of the study reveal that 1) using different teaching methods and planning what lessons will be taught related to psychological development, 2) the obstacles faced in maintaining the psycological development of early childhood are when dealing with children whose IQ is weak, be patient in dealing with it because at an early age it is different from those who are already in elementary school. 3)Supporting factor for early childhood development. such as learning media that exist in the institution itself, such as game tools, APE, module books, and drawing tools, which are all very supportive for students.